The Fractured image exploring identities. (Lincolnwood, Ill. National Textbook Co., 1999)
Presents annotated works of fiction addressing the topic of identity and a section of related articles with discussion questions.
Keywords: Readers (Secondary); Identity (Psychology) in literature -- Problems, exercises, etc; Psychological fiction -- Problems, exercises, etc; Identity (Psychology) -- Fiction; Readers